GENDER REPRESENTATIONS IN INDONESIAN ENGLISH LANGUAGE TEACHING (ELT) TEXTBOOK TITLED “BAHASA INGGRIS UNTUK SMA/MA/SMK/MAK KELAS X” - Rizqoh Fadila Ramadani; Maria Novianti (ELTR Journal, 2021)
AbstractGender inequality issues are issues that are still often found in daily life. Evidently, the issues do not only happen in the action of real-life but previous researches have also discovered that gender inequality does exist in textbooks in the form of how genders are being represented unequally. With this gender representations issue emerging, this research aims to identify and analyze the gender representations in the ELT textbook titled “Bahasa Inggris Untuk SMA/MA/SMK/MAK Kelas X”. It is important to know if the genders are being represented equally because the books which exclude one or more gender can affect its readers and or users. To reach the goal stated this research used a qualitative method with a content analysis approach. The analysis of the data which was taken both from the texts as well as from the illustrations shows that there are many characteristics that only represent a specific gender and not the others. From the occupational activities that are only explored often by men, to domestic items that are attached to women. It can be concluded that the BI textbook has not represented genders equally. Some genders are stillexcluded in several activities, attributes, and designations.